Novo Ensino Médio: redesenho curricular inovador no contexto da Base Nacional Comum Curricular - Braun, Rachel de Oliveira (2022)
The New High School curriculum of the Community School, built in partnership with the principals, coordinators, teachers and students, concludes in 2022 a work started in 2019 with the objective of meeting the changes determined by Law 13.415/2017, which guided the High School Reform. This Law imposed the need for a reorganization in a National Common Curricular Base (BNCC) of High School, which was disciplinary and has started to be structured in two parts: (1) Basic General Training (BGT), structured in areas of knowledge; and (2) Training Itineraries, which meet the expectations of students. In 2018, the National Education Council (NEC) issued an opinion updating the High School Curriculum Guidelines (HSCG) so that changes could be implemented in schools all over the country. In this thesis, concepts for the understanding of the New High School will be addressed, as well as a new planned curricular structure, considering one of its greatest innovations: the Formative Itineraries. The curricular structure set up by the pedagogical team of the Community School reflects the principles already consolidated for the new High School, such as integral training, respect for diversity, scientific research as a pedagogical practice, allowing greater flexibility in the formation of the student and offering the possibility of experiencing several professional aspects and a possible improvement in qualified employability that allows him not only to enter higher education, but also to be able to remain there until graduation. In this way, the innovative curriculum of the Community School was elaborated from active listening and a lot of collaboration from the entire school community. The main objective of this thesis is to organize a New High School curriculum that makes sense for students, that contributes to their integral and citizenship training and that can improve their employability, reducing the high rates of dropout from school and contributing to the realization of their life projects. The theoretical framework used for the research work were the BNCC guiding documents, the theoretical studies of educational curricula prepared by Sacristán and Zaballa, and the studies on innovative curricula by Masetto, Gaeta and Thüler. The research had a qualitative approach of the participant type